Flash functional group-tolerant biaryl-synthesis based on integration of lithiation, zincation and negishi coupling in flow - Ashikari, Yosuke; Guan, Kaiteng; Nagaki, Aiichiro (Frontiers in Chemical Engineering, 2022)
We achieved an integration of a lithiation of aryl bromides, a zincation of thus-generated aryllithiums, and a Negishi coupling of the arylzinc with an aryl halide in one flow. Taking advantages of flow microreactors, biaryls bearing a wide range of functional groups, especially biaryls bearing multiple electrophilic-functionalities were synthesized.